Two novel mutations with 17 hydroxylase deficiency – Alpha and beta presenting as 46XY disorders of sexual development - Lohiya, Nikhil; Khadilkar, Vaman; Mehta, Kamini; Khadilkar, Anuradha (Indian Journal of Child Health, 2019)
17 alpha-hydroxylase and 17 beta-hydroxylase deficiency are rare causes of 46XY disorders of sexual development. The gene for 17 alpha-hydroxylase enzyme (CYP17A1) is located at 10q24.3 and for 17 beta-hydroxylase is (17?HSD3) on 9q22. CYP17A1 can present with delayed puberty and hyporeninemic, hypokalemic hypertension. In 17?HSD3 deficiency, a biochemical pointer to diagnosis includes a stimulated ratio of testosterone (T) to androstenedione (A) of <0.8. We report two cases, one with 17?HSD3 defect in infancy with atypical genitalia and second with CYP17A1 which presented in childhood with novel mutations. There is a wide spectrum of phenotypic presentations of these disorders. Genetic analysis gives confirmation.